2020
DOI: 10.1177/2042018820958322
|View full text |Cite
|
Sign up to set email alerts
|

Hemodialysis patients with low serum parathyroid hormone levels have a poorer prognosis than those with secondary hyperparathyroidism

Abstract: Background: Low serum parathyroid hormone (PTH) level and secondary hyperparathyroidism (SHPT) are very common in hemodialysis patients. However, the outcomes of patients with low PTH level or SHPT have not been carefully compared. Therefore, in the present study, we compared the outcomes of hemodialysis patients with low PTH level or SHPT. Methods: This was a multi-center, prospective, cohort study of 647 patients. The patients were recruited between 1 September 2016 and 1 January 2017 and followed until 31 D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 29 publications
0
19
1
Order By: Relevance
“…preprint (which was not certified by peer review) is the author/funder, who has granted medRxiv a license to display the preprint in The copyright holder for this this version posted September 23, 2021. ; https://doi.org/10.1101/2021.09.21.21263568 doi: medRxiv preprint Laboratory variables were remarkable in this study. Low iPTH has been previously proposed as a marker of malnutrition and inflammation and established as a poor prognostic factor in HD patients [15][16][17][18][19] . It has also been proposed that a low iPTH is related with immunologic dysfunction, with a higher risk of infection in ESRD patients 19 .…”
Section: Discussionmentioning
confidence: 99%
“…preprint (which was not certified by peer review) is the author/funder, who has granted medRxiv a license to display the preprint in The copyright holder for this this version posted September 23, 2021. ; https://doi.org/10.1101/2021.09.21.21263568 doi: medRxiv preprint Laboratory variables were remarkable in this study. Low iPTH has been previously proposed as a marker of malnutrition and inflammation and established as a poor prognostic factor in HD patients [15][16][17][18][19] . It has also been proposed that a low iPTH is related with immunologic dysfunction, with a higher risk of infection in ESRD patients 19 .…”
Section: Discussionmentioning
confidence: 99%
“…In their study, Yu et al show that hemodialysis patients with low PTH level (<60 pg/ml) had a higher incidence of mortality and non-fatal cardiovascular events than those with SHPT (>600 pg/ ml). 9 Authors found a significant difference in age between the two groups, but the incidence of the composite outcome remained significantly higher in the low PTH group than in the SHPT group (50% versus 27.8%). Interestingly, these data reflect results that we published a few years ago, 10 from the analysis of the FARO survey, suggesting that low doses of paricalcitol an active vitamin D treatment associates with reduced overall mortality as well as factor-adjusted mortality risks among dialysis patients with SHPT, even when serum iPTH levels are ⩽150 pg/ml.…”
mentioning
confidence: 93%
“…In summary, Yu and coauthors are showing that, in dialysis patients serum, PTH levels lower than 100 pg/ml are associated with poor outcomes. 9 Therefore, all the causes that potentially contribute to over-suppress PTH, such as high Ca concentration in dialysis bath, high doses of calcium-based P-binders, and high doses of active vitamin D and/or calciminetics, should be considered in this population. Low doses of vitamin D might be maintained.…”
mentioning
confidence: 99%
“…Bone and mineral disorders caused (BMD) by CKD, Low/high serum PTH level and secondary hyperparathyroidism (SHPT) are very common in hemodialysis patients (Yu et al, 2020). The derangement is usually accompanied by profound changes in mineral metabolism and has been linked to poor control of hyperphosphatemia, leading to the increased risk of vascular calci cation inhibitors (Jorge, n.d,2010), serum calcium and Parathyroid hormone (PTH, a major, systemic, calciumregulating hormone) homeostasis that leads to the increased risk for the progression of cardiovascular morbidity and bone disorder (Zhang & Li, 2020) and has emerged as important predictors to be associated with all-cause mortality and morbidity in dialysis patients.…”
Section: Introduction 11 Background Of the Studymentioning
confidence: 99%